Enzyme-linked immunosorbent assay for identification of infectious pancreatic necrosis virus. - Nicholson, B L (1982)
The sensitivity, reproducibility, and specificity of an enzyme-linked immunosorbent assay for the identification of infectious pancreatic necrosis virus was determined. It was shown that 10(5.5) tissue culture infectious doses could be assayed by this method. The assay provided significant advantages in terms of time and ease of performance over the routinely employed serological tests. When an antiserum against a single isolate was used, it was possible to identify nine of ten North American isolates, four of six European isolates, and one isolate from Taiwan.